Histological Effects of Titanium Dioxide Nanoparticles Size 10 Nm in Mice Testes - Abdulla, Imad T. (Science Journal of University of Zakho, 2017)
In the present study, the histological effect of titanium dioxide nanoparticles (TDN) on testicular tissue of mature Mus musculus mice was investigated. The animals were divided into six groups, control group treated with TDN free saline and five groups treated with TDN as follow 5, 10, 50, 100 and 150 mg/kg B.W. The results showed that TDN has histological effects on testicular tissue like sever congestion, mild edema between seminiferous tubules (STs) and decrease the thickness of germinal epithelium at low concentrations, While, the histological changes at high concentrations involved disturbance in STs diameters, sever edema between STs, sever vaculation in the germinal epithelium and necrosis in spermatogonia, germinal epithelium and Sertoli cells.